Polyunsaturated fatty acids in human milk: an essential role in infant development - Innis, Sheila M (Advances in experimental medicine and biology, 2004)
The n-6 and n-3 fatty acids are essential dietary nutrients required for optimal growth and development, particularly of the brain and retina. Large amounts of the n-3 fatty acid docosahexaenoic acid (DHA) is accumulated in the brain grey matter and the visual elements of the retina during development, and reduced DHA in these tissues can result in decreased visual and psychomotor development. Although the possible importance of differences in n-6 and n-3 fatty acids, particularly DHA, between human milk and infant formulas has been the subject of intense clinical research, the variability in the essential fatty acid content of milk within and among different populations of women and implications of this to infant growth and development have received much less attention. Considerable research has shown that the DHA content of the maternal diet is the most important determinant of the amount of DHA secreted in milk, and thus the dietary intake of the breastfed infant. The DHA content of human milk varies over 10-fold, being lowest in women with no intake of DHA and highest in women with high intakes of DHA, which is found predominantly in fatty fish. The requirement for n-3 fatty acids, and the balance of n-6 and n-3 fatty acids for optimal growth and development of the brain and retina, and long-term minimization of risk of chronic disease remains as one of the most important questions in infant nutrition. Dietary recommendations to modifying dietary fat with the aim of reducing risk of chronic disease, including obesity and cardiovascular disease in adults, need to consider that when followed by pregnant women, these recommendations can have a marked effect on the amount and balance of n-6 and n-3 fatty acids secreted in milk.